PENGARUH METODE GUIDED DISCOVERY LEARNING TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2011/2012 - Melani, Riyan; Harlita, Harlita; Sugiharto, Bowo (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The purposes of this research are to ascertain: 1) the influence of guided discovery methode toward scientific attitudes and 2) the influence of guided discovery learning methode toward student?s achievement in cognitive domain. The research was quasi experiment research. The research was designed using randomized control-group pretest-postest design. Experimental group applied guided discovery method. Control group applied conventional metode. The populations of this research were all of 10th degree students at SMA Negeri 7 Surakarta in academic year 2011/2012. The samples of this research were the students of X2 as control group consist of 30 students and X3 as experiment group consist of 31 students. The sample of this research was established by cluster random sampling. The scientific attitudes data was collected by questionaire and the student?s achievement in cognitive domain was collected by essay test. The hypotheses of scientific attitudes data analyzed by t test and the student?s achievement in cognitive domain data analyzed by anacova. The conclusions of this research are: 1) application of guided discovery learning method had significant effect toward scientific attitudes; 2) application of guided discovery learning method had significant effect toward student?s achievement in cognitive domain. Keywords: guided discovery methode, scientific attitudes, cognitive achievement of Study in Biology